Effective Music Practice. Equipping Students with the Tools to Succeed - Capistrán-Gracia, Raúl Wenceslao (Grenek: Jurnal Seni Musik, 2024)
By showing their musical achievements in concerts, auditions, competitions and the like, music students are not only executing notes, but they are exhibiting their aspirations and exposing their affective dimension. Many times, their personal dreams, as well as their own professional future are put at a stake with the resulting social and affective consequences. This represents a great responsibility for teachers since, as educators, they must provide their students with the necessary tools to succeed in their endeavor. In this essay, the author provides an overview on different music practice strategies whose effectiveness have been tested in rigorous research studies or proved by experienced teachers. The author expects they may be helpful to teachers and students to overcome the musical challenges the learning of music and its public performance entails.